Mycetoma and the Community Dermatology Program, Mexico. (21st January 2021) - Roberto, Estrada; Guadalupe, Chávez-López; Guadalupe, Estrada-Chávez; Hay, Roderick
Abstract: The Community Dermatology Program established in the state of Guerrero, Mexico for almost 30 y provides an adaptable method of detecting and monitoring skin neglected tropical diseases such as mycetoma, which is endemic in the state. The program utilises general and thematic teaching elements combined with distance learning through teledermatology, direct patient consultations and close collaboration with community teams. Using this approach, a picture of mycetoma in Guerrero has emerged, with a focal hot spot located in the southern part of the state in the Costa Chica region. Although in much of Mexico Nocardia infections dominate, in this area there are also substantial numbers of cases of eumycetoma. This combined approach provides a means of early case detection and long-term surveillance through targeted use of a small specialist team.